Comparing college students' mood states among immersive virtual reality, non-immersive virtual reality, and traditional biking exercise. - Wenxi Liu; Daniel J McDonough; Zan Gao (PLoS ONE)
Objectives This study examined differences in young adults' mood states during immersive virtual reality (VR), non-immersive VR, and traditional exercise biking sessions. Design Repeated-measure study design. Methods Forty-nine college students (34 females; Mage = 23.6 years) completed three separate 20-minute exercise biking sessions: (1) immersive VR biking using the PlayStation 4 + VirZoom VR bike; (2) non-immersive VR biking using the Gamercize bike + Xbox 360; and (3) traditional stationary biking using the Spirit Fitness XBU55. Participants' mood states (anger, confusion, depression, fatigue, tension, and vigor) were assessed by using the Brunel Mood Scale after each session. Results Statistically significant differences were observed between biking sessions for all components of mood [F (2, 96) = 3.84-278.56, p < 0.05, η2 = 0.07-0.85], except for tension (p > 0.05). Results indicated non-immersive VR biking yielded significantly higher anger compared to immersive VR biking; non-immersive VR biking yielded significantly higher confusion compared to immersive VR biking and traditional biking, respectively; immersive VR biking yielded significantly lower depression compared to traditional biking; both immersive VR biking and non-immersive VR biking yielded significantly lower fatigue compared to traditional biking; and immersive VR biking yielded significantly higher vigor compared to non-immersive VR biking) and traditional biking, respectively. Conclusion Findings suggested the immersive VR-based biking exercise may facilitate in reducing the negative feelings, such as anger, fatigue, depression, and improving positive feeling, such as vigor, among college students. The immersive VR-based exercise appeared to be a feasible approach for motivating college students participating in physical activity and improving overall mood states.